FEEDBACK BETWEEN DEFORMATION AND MAGMATISM IN THE LLOYDS RIVER FAULT ZONE: AN EXAMPLE OF EPISODIC FAULT REACTIVATION IN AN ACCRETIONARY SETTING, NEWFOUNDLAND APPALACHIANS - Lissenberg J.C.; Van Staal C.R. (My University, 2006)
The Lloyds River Fault Zone is a 10-15 km wide amphibolite-grade shear zone that formed during the Ordovician Taconic Orogeny. It separates ophiolites and arc-back-arc complexes formed in lapetus from a periLaurentian microcontinent (Dashwoods microcontinent). The Lloyds River Fault Zone comprises three high-strain zones, dominantly composed of mylonitic amphibolites, separated by less deformed plutonic rocks. Structural, age and metamorphic data suggest the Lloyds River Fault Zone accommodated sinistral-oblique underthrusting of ophiolites underneath the Dashwoods microcontinent prior to 471 ± 5 Ma at 800°C and 6 kbar. Plutonic rocks within the Lloyds River Fault Zone comprise two suites dated at 464 ± 2 plus 462 ± 2 and 459 ± 3 Ma, respectively. The younger age of the plutons with respect to some of the amphibolites, evidence for magmatic deformation, and the elongate nature of the plutons parallel to the Lloyds River Fault Zone suggest they were emplaced within the fault zone during deformation. Both intrusive episodes triggered renewed deformation at high temperatures (770-750°C illustrating the positive feedback between deformation and magmatism. Offshoots of the plutons intruded undeformed ophiolitic gabbros outside the Lloyds River Fault Zone. Deformation localized within the intrusive sheets, coeval with static contact metamorphism of the host gabbros, leading to the development of new, small-scale shear zones. This illustrates that channeling of plutons into shear zones and nucleation of shear zones in melt-rich zones may occur simultaneously within the same fault system.